POTENSI STEVIA SEBAGAI PEMANIS NON KALORI PADA YOGHURT - Kun Harismah; Shofi 'Azizah; Mutiara Sarisdiyanti; Rahmawati Nurul Fauziyah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Sucrose plays a significant role in many dietary health problems such as diabetes mellitus,coronary heart disease, and obesity. Consumption of sucrose has now become more prevalent.Stevia rebaudiana Bertoni is one of the most non caloric natural sweeteners known to mankind.The dried leaves of stevia sweetness level 30 times sweeter than sucrose. Yogurt is one of thefood products that utilize microorganisms to produce certain components in order to obtain thepeculiarities of texture, flavor, color and aroma. In this study, yogurt supplemented with sucroseand stevia sweetener with various concentrations. Variable one contained 100% sucrose wasmade for a comparison along with four additional variables. The variables consisted of sucroseand stevia 1:1, 1:2, 1:3, and 0:4. The five samples were measured and their effects on sensoryacceptability and caloric of product were investigated. The results revealed that the highestcaloric contained in yogurt with added sucrose 100 %, while the lowest caloric contained in theyogurt with the addition of stevia 100 %. The amount of calorie was reduced by 68.05%,indicating that stevia has a good potential to be exploited as an alternative sweetener foryoghurt. Results also revealed that sensory acceptability panelists prefer the yoghurt with theaddition of sucrose compared with stevia. Keyword: sucrose, stevia, yoghurt, non calorie